2021
DOI: 10.3390/en14175529
|View full text |Cite
|
Sign up to set email alerts
|

Organic Dyes in Dye-Sensitized Solar Cells Featuring Back Reflector

Abstract: Dye-sensitized solar cells (DSSCs) were fabricated using a photoelectrode covered by a porous layer of titanium dioxide, platinum counter electrode, iodide/triiodide electrolyte and three different dyes: phenylfluorone (PF), pyrocatechol violet (PCV) and alizarin (AL). After the adsorption of the dyes on the mesoporous TiO2 layer, the measurement of absorption spectra of all the tested dyes revealed a significant broadening of the absorption range. The positions of highest occupied molecular orbital (HOMO) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…These results agree with the existing literature for DSSC back reflectors. Zdyb and Krawczak, for instance, achieved a 15.7% increase in PCE with a 19.7% increase in J SC by using BaSO 4 as a back reflector on DSSCs using N719 dye, and obtained even larger increases in PCE when used on alternative sensitizing dyes [52]. This speaks to the promise that highly reflective materials have for increasing light harvesting in solar cells.…”
Section: Discussionmentioning
confidence: 95%
“…These results agree with the existing literature for DSSC back reflectors. Zdyb and Krawczak, for instance, achieved a 15.7% increase in PCE with a 19.7% increase in J SC by using BaSO 4 as a back reflector on DSSCs using N719 dye, and obtained even larger increases in PCE when used on alternative sensitizing dyes [52]. This speaks to the promise that highly reflective materials have for increasing light harvesting in solar cells.…”
Section: Discussionmentioning
confidence: 95%
“…It was suggested that the nucleation and conjoining of microscopic particles are responsible for the development of such porous structures [8]. It is the mesoporous TiO2 layer that aids in the increased adsorption of dye molecules, as well as the increased penetration into the TiO2 layer by the electrolyte [9].…”
Section: Surface Morphology Fesem/ Edx and Xrdmentioning
confidence: 99%
“…Investigation of the optical properties of push-pull dyes is notably justified by the number of applications requiring push-pull dyes. Thus, push-pull dyes have been extensively used in photopolymerization [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ], non-linear optics [ 4 , 5 , 44 , 45 , 46 , 47 , 48 , 49 ], light-to-energy conversion [ 6 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], biological labelling [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ], light-emitting diodes [ 65 , 66 , 67 ] or cell nucleus staining [ 68 , 69 ]. Among electron donors that have only been scarcely used for the design of push-pull dyes, pyrene is one example.…”
Section: Introductionmentioning
confidence: 99%